1а)7,9 б)-3,5 в)6 2.а)3 б)12 в)3 г)20 3. а)х=±0,8 б)х=±√17 4.а)2у в 4 степени; б)-28 5. 6,1∠√38∠6,2 6. х=3
Объяснение:√196=14, √0,36=0,6
а)1/2 *14+1,5* 0,6=7+0,9=7,9
б)1,5-7 * 5/7=1,5 -5=-3,5
в)(2√1,5)²=2²*(√1,5)²=4* 1,5= 6
2.а) √0,36*25=√0,36 *√25=0,6*5=3
б)√8*√18=√(4*2*2*9)=4*3=12
в)√27/√3=√(27/3)=√9=3
г)√〖2^4〗*〖5^2〗=2²*5-4*5=20
3.а) х²=0,64
х=±0,8
б)х²=17
х=±√17
4.а) у³√4у²=у³*2у=2 у∧4
б)7а √(16/а²)=-7а* (4/а)=-28
5. 6²=36
(6,1)²=37,21
(6,2)²=38,44
6,1∠√38∠6,2
6.√(х-2)=1 поднесем до квадрата обе части уравнения
х-2=1
х=1+2
х=3
(8x-y)²-64x²=64x²-16xy+y²-64x²=y²-16xy
2(a-b)²=2a²-4ab+b²
-y(3x-y)²= -9x²y+6xy²-y³
a(4-a)+(4-a)²=4a-a²+16-8a+a²=-4a+16
9x²-(y-3x)²=9x²-y²+6xy-9x²=-y²+6xy
(5a+7)²-70a=25a²+70a+49-70a=25a²+49
c(1+2c)²=c+4c²+4c³=4c³+4c²+c
-6(2x-y)²=-24x²+24xy+6y²
(p+7)p-(1-p)²=p²+7p-1-2p+p²=2p²+7p-1